2021
DOI: 10.3389/fpsyt.2020.607811
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Serious Suicide Attempts: Difference Between Older and Younger Attempters in the Emergency Department

Abstract: Objective: Suicide attempts of the older adults are known to be more serious than that of the younger adults. Despite its major social impact in South Korea, the behavioral mechanism of serious suicide attempt (SSA) in old people remains to be elucidated. Thus, we investigated the risk factors for SSA in older and younger suicide attempters in the emergency department.Methods: Demographic data, clinical information, and the level of seriousness of suicide with Risk Rescue Rating Scale were compared between old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
(64 reference statements)
1
4
0
Order By: Relevance
“… 12 One study of the RRRS reported that old age, male sex, alcohol intoxication, the presence of interpersonal stress, and a history of schizophrenia were independent factors associated with the risk-rescue ratio in individuals younger than 65 years of age. 15 In this study, age was also an independent factor associated with low-rescue suicide attempts, which was consistent with previous studies. The pandemic may not have had an equal effect on the whole population of suicide attempters; for instance, it may have had more negative effects on some vulnerable individuals related to social isolation and social lockdown.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“… 12 One study of the RRRS reported that old age, male sex, alcohol intoxication, the presence of interpersonal stress, and a history of schizophrenia were independent factors associated with the risk-rescue ratio in individuals younger than 65 years of age. 15 In this study, age was also an independent factor associated with low-rescue suicide attempts, which was consistent with previous studies. The pandemic may not have had an equal effect on the whole population of suicide attempters; for instance, it may have had more negative effects on some vulnerable individuals related to social isolation and social lockdown.…”
Section: Discussionsupporting
confidence: 92%
“…These variables are known clinical factors with significant correlations with suicide attempt lethality or risk-rescue ratio on the basis of a previous studies. 12 13 14 15 The Hosmer–Lemeshow test was confirmed for goodness of fit for logistic regression models. The results are presented as odds ratios (ORs), 95% confidence intervals (CIs), and P values.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…Therefore, this study defined the term "suicidal crisis" as "clients with suicide attempts with suicide intention" as the client's intention has been inspected as the crucial variable in suicide attempts (51). Also, suicide attempts in one's history have been the most predictive variable for later completed suicide, and it has been a strong indicator of increasing the risk of actual suicide with more fatal methods at a later stage (23,24,(52)(53)(54)(55).…”
Section: Participantsmentioning
confidence: 99%
“…However, to our knowledge, no such study has been published. In recent years, the RRRS has occasionally been used as an outcome measure of the severity of suicidal attempts (Oh et al, 2015;Kim et al, 2021), but no recent studies have assessed its reliability and validity.…”
Section: Introductionmentioning
confidence: 99%